2019
DOI: 10.1039/c9ra01662g
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hydrothermal pre-treatment on the anaerobic digestion of different solid–liquid ratio sludges and kinetic analysis

Abstract: This study is an assessment of hydrothermal pre-treatment (HTP) of different solid–liquid ratio (SLR) sewage sludge for enhancement of biogas production by anaerobic digestion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 52 publications
1
21
0
Order By: Relevance
“…Consequently, targeted fermentation product from microbial process is improved considerably. [ 37 ] Furthermore, ABE fermentation of pretreated algal biomass ( Gracilaria tenuistip ) by Low‐HTP under the R 0 lower than 2.07 could obviously provide satisfy either ABE or butanol production yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, targeted fermentation product from microbial process is improved considerably. [ 37 ] Furthermore, ABE fermentation of pretreated algal biomass ( Gracilaria tenuistip ) by Low‐HTP under the R 0 lower than 2.07 could obviously provide satisfy either ABE or butanol production yield.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, targeted fermentation product from microbial process is improved considerably. [37] Furthermore, ABE fermentation of pretreated algal biomass (Gracilaria TA B L E 4 Production by Gracilaria tenuistipitata under low-HTP. −1 ] T e m p [ As can be seen from our results, C. beijerinckii did not use all the sugars; hence, it could only produce a small amount of butanol.…”
Section: S/l Ratio [G Lmentioning
confidence: 99%
“…2013; Gong et al . 2019). This parameter has also been optimized in attempts to decompose oily sludge (Xu et al .…”
Section: Discussionmentioning
confidence: 99%
“…For PsNPs exposure experiments, 150 μg/L PsNPs were prepared and added to the PS with different TS% (4, 8, and 12%). According to the literature, recent studies examining the impact of TS% on THP efficiency selected 2–15% as their appropriate operating TS content. , Thereby, the TS content in this range was selected. As reported in a previous study, 150 μg/L PsNPs could have a more detrimental effect on AD than 50 and 100 μg/L .…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies previously emphasized the significance of TS% on the efficiency of the THP process in terms of solubilization and its subsequent impact on AD . For instance, Gong et al found that the THP of sludge with 8% TS was the most advantageous among different TS% (5, 8, 10, 12, and 15%), resulting in the highest levels of sludge disintegration and methane production . Similarly, Li and Chen found that 6% TS was the most effective within a wide range of TS% (2 to 12%) in enhancing THP efficiency regarding sludge solubilization and methane production .…”
Section: Introductionmentioning
confidence: 99%